Entrepreneurial Characteristics and Entrepreneurial Orientation in Improving Business Performance of MSME Trading Assisted by the Surabaya Trade Office - Achmad Daengs GS; Enny Istanti; Retno Susanti (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: Analyze the effects of entrepreneurial characteristics on business performance through entrepreneurial orientation. Type of the research is causal research. Design/methodology/approach: Analysis performed under quantitative analysis by using SEM Analysis and PLS to resolve the problem formulation and to know the effect of the determined variables. Findings: The study result show that: (1) Entrepreneurial Characteristics affects the Entrepreneurship Orientation of MSME business actors; (2) Entrepreneurial Characteristics does not affect the Business Performance of MSME business actors; (3) Entrepreneurship orientation affects business performance in MSME business actors. Practical implications: Intensify the effort under economic field in order to improving the income. Originality/value: Originality here. Paper type: Research paper